(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In the world of marketing, the word femvertising plays a dramatic change in India which influences the women consumers’ perception towards the gender portrayal of advertising.In today’s advertisement the women empowerment has a great impact in the purchase behaviour of the products which in turn it generates profit for the business and also it createsgender equality in the society where it becomes the leading theme in the advertisement sector. Most of the advertisement projects more on women and gives equal rights with irrespective of gender and the marketer’s started portraying women as a strong independent. This article investigates how the perception of women towards the stereotype advertising in the modern era and how it explores the awareness of Indian consumers in the area of online clothing stores.